Turkish folk medicinal plants, Part IV: Gönen (Balikesir) - (:unkn) unknown (My University, 2001)
Eighty-four folk medicinal plants from Gönen (Turkey) are reported. Among them 73 species are wild and 11 species are cultivated plants. The folk medicinal plants are mostly used for the treatment of hemorrhoids, rheumatism, stomach and kidney ailments.
Keywords: Humans; Turkey; Plants, Medicinal; Medicine, Traditional